The Russian Revolutions of 1917 : the northern impact and beyond - Myklebost, Kari Aga; Nielsen, Jens Petter; Rogatchevski, Andrei (2020)
In October 2017, UiT - the Arctic University of Norway hosted the international conference The Russian Revolutions of 1917: The Northern Impact and Beyond. The aim was to explore the events of 1917 in Russia, with a particular focus on the northern regions and the impact on Russia's neighbor state in the northwestern corner of the empire, Norway. The conference also included contributions that reach beyond the North, opening up for more general perspectives on the revolutionary events of 1917 and their impact in Europe, as well as Russia. Several contributions contain a bilateral perspective, discussing the reception of the Russian revolutions of 1917 in Scandinavian states and the significance of these events for the bilateral relations between various states